Terahertz focusing blazed diffractive optical elements for frequency demultiplexing - Kaluza, Mateusz; Komorowski, Paweł; Zagrajek, Przemysław; Siemion, Agnieszka (Advanced Optical Technologies, 2023)
This study presents the novel optical passive components for spatial frequency division demultiplexing of terahertz (THz) radiation. Four different diffractive optical elements (DOEs) were designed as the combination of phase kinoform lenses and phase blazed diffraction gratings. The designed structures were verified in numerical simulations and they showed the promising results. Subsequently, they were manufactured using fused deposition modeling (FDM) 3D printing technology from highly transparent cyclic olefin copolymer (COC). The manufactured structures were examined in the experimental setup. The results matched numerical simulations. Thus, eight frequencies in the range from 150 GHz to 220 GHz every 10 GHz were spatially separated. The novel design solution guaranteed 63% higher relative efficiency compared to the reference DOE.The presented study can be suitable as the application for 6G technology telecommunication systems as the spatial frequency division demultiplexing component for the THz radiation band.